Factores relacionados con situaciones de abuso en la Iglesia católica peruana - Zapata-Pratto, Dafne (Teología y vida, 2024)
A qualitative research study was undertaken to explore the factors that lead to and sustain abuse in the Peruvian Church. Cultural factors (abuse of power, normalization of violence, and hegemonic masculinity), ecclesiastical factors (clericalism, rigid hierarchical differences in relationships and in the understanding of how to be Church, and structural Church factors that show up in the Peruvian context), and educational factors were identified. Although the findings represent significant challenges for the Church, there is recognition of the progress that has been made in certain institutional sectors in terms of education, prevention efforts, and openness to reflecting on power and relationships.